ELECTRONIC MICROSCOPY STUDIES ON THE ADHESION OF TOTAL ETCH ADHESIVE SYSTEMS IN GLASS-IONOMERS AND COMPOMERS - Cristina-Angela Ghiorghe; Gianina Iovan; Mihaela Sălceanu; Antonia Moldovan; Cristina Iordache (Romanian Society of Oral Rehabilitation, 2017)
The aim of this study was to evaluate in vitro the adhesion and the type of bond failure when compomer or glass-ionomer cement was bonded with resin composite to total etches system. Scanning Electron Microscopy (SEM) was used for tested the compomer Dyract eXtra (D) and glass-ionomer cement Ketac Molar Easymix (KM) as basic restoration under two types of composite resins mycrohibride with total etch adhesive. A total number of 30 human molars were prepared with standardised cavities and were randomly divided in 3 groups. In the control group (F/Z), the cavities were filled only with composite resins (Filtek Z250-3M ESPE or Zmack Comp-Zermack). In group test 1 (G1 F-D/ G1 F-KM) the cavities were filled with Filtek Z250 in combination with Dyract, respectively Ketac Molar Easymix (as basic restoration). In group test 2 (G2 Z-D/G2 Z-KM) the cavities were filled with Zmack Comp in combination with Dyract, respectively Ketac Molar. The teeth were kept in distilled water at 37 ° C for 24 hours. The samples were longitudinally sectioned through the restoration and exposed to electron microscopy to see the adhesion of these materials to the dental tissues but also between them. The results indicated the bond strength of the composite resin to the conventional glassionomer cement was lower than that to the resin-modified glassionomer cement.